Causal relationships among perception of errors, challenges, and deliberate practice in athletes with disabilities - Sim, Young Kyun; Shin, Joon Ha; Kim, Song Eun; Seo, Eun Chul; Ha, Min-Seong (Frontiers in Psychology, 2024)
There is limited evidence that the psychological characteristics of athletes with disabilities are identical to those of non-disabled athletes, owing to differences in ecological traits, and there is insufficient information on how athletes with disabilities perceive disabled athletes' perception of errors, challenges, and deliberate practice.Therefore, it is necessary to examine whether the causal model of the perception of errors, challenge, and deliberate practice will be reproduced in the same way as in non-disabled athletes. Therefore, this study aimed to verify a causal model of the perception of errors, challenges, and deliberate practice by athletes with disabilities.The participants were 189 athletes with physical and hearing impairments (131 men and 58 women) registered with the 2023 Korea Paralympic Committee. Data were collected through a survey and the participants responded using a self-report method. The collected data were analyzed using descriptive statistics to verify normality, correlation analysis to examine relationships between variables, and structural equation modeling (SEM) to test the hypotheses.Based on SEM analysis, the results of this study showed that the causal relationships between the perception of errors, challenges, and deliberate practice were partially significant. Specifically, perception of errors and reflection positively predicted challenges, whereas burden of mistakes negatively predicted challenges. Additionally, challenges were found to have a positive effect on deliberate practice. Discussion: By comprehensively examining the above, it can be interpreted as a major factor that can promote and reduce challenges depending on how athletes with disabilities perceive their mistakes.